Model Test and Numerical Simulation Analysis on Freezing Effect of Different Freezers in Freeze-Sealing Pipe-Roof Method - Haibing Cai; Yujie Liu; Rongbao Hong; Mengkai Li; Zongjin Wang; Hanglong Ding (Geofluids)
The Gongbei Tunnel Project is a key phased project of the Zhuhai Connection Line of the Hong Kong–Zhuhai–Macao Bridge, and the freeze-sealing pipe-roof (SFPR) method was first applied successfully. During this period, in order to obtain the best arrangement of freezers, three configurations, that is, solid pipe with circular freezer (SCF), empty pipe with double circular freezer (EDCF), and empty pipe with special-shaped freezer (ESF), were designed to analyze their freezing effects. The model test results show that the freezing temperature fields excited by different arrangements of freezers are obviously different, and the freezing effect of ESF is the best. The numerical simulation results indicate that the temperature cloud diagram of SCF at 42 h is butterfly-shaped after opening the limit pipes, and the temperature cloud diagrams of ESF and EDCF are the same as the model test results. However, the processing method of ESF is relatively complex, which adopts arc angle steel welding requiring a lot of reverse welding and high welding quality. Eventually, EDCF is recommended to ensure the quality of frozen walls due to its lower cost and better freezing effect. This research plays a basic role in the implementation of the freeze-sealing pipe-roof method.